2019
DOI: 10.5812/jjm.66502
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity Identification of a Novel Recombinant Multi-Epitope Antigen Based on FlaA and UreB Antigens of Helicobacter pylori

Abstract: Background: Helicobacter pylori is the main cause of stomach ulcers and gastric cancer. Hence, the diagnosis, treatment, and prevention of H. pylori infection can considerably reduce the fatality. Objectives: This study aimed to construct a dual-antigen protein by combining the antigenic regions of UreB and FlaA of H. pylori and determine its antigenicity as a promising vaccine and serodiagnosis candidate. Methods: The antigenic regions of FlaA and UreB were detected by immunological bioinformatics, amplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The induction result was confirmed by transferring the resulting protein to the (12%) Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gel. Finally, the extraction of synthesized recombinant protein was performed by using Ni-NTA kit (Qiagen, USA), according to the manufacturer's instructions (14,15).…”
Section: Cloning Expression and Purification Of Recombinant Protein mentioning
confidence: 99%
“…The induction result was confirmed by transferring the resulting protein to the (12%) Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gel. Finally, the extraction of synthesized recombinant protein was performed by using Ni-NTA kit (Qiagen, USA), according to the manufacturer's instructions (14,15).…”
Section: Cloning Expression and Purification Of Recombinant Protein mentioning
confidence: 99%
“…Epitope-based vaccines are more cost-effective than mixed proteins and can cover more protein targets, so multiepitope vaccines receive more attention. 91 …”
Section: Discussionmentioning
confidence: 99%
“…The recombinant protein can be recognized in the sera of patients with H. pylori infection with high sensitivity and specificity. 91 …”
Section: Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…UreB has been detected in the bacteria cytoplasm and periplasm (Marcus et al 2013 ), but also on the bacteria surface (Haas et al 2000). Flagellin A (FlaA) is a motility factor, involved in the colonization of the host and on the inflammatory processes (Gu et al 2017 ) and has been suggested as a good vaccine target (Yan et al 2003 ; Hamzehloo et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%